2015
DOI: 10.1007/978-3-319-20484-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Linear Mixed-Effects and Latent Curve Models for Longitudinal Life Course Analyses

Abstract: The core of life course or lifespan research consists in studying how individual trajectories are shaped and unfold over time, from conception to death (Baltes 1987). Two concepts are fundamental in this endeavor: stability and change. Indeed, while certain individual characteristics remain constant across one’s lifespan (e.g., sex, ethnicity), others undergo profound change, to the point that they might mutate into other characteristics (e.g., health, cognitive capacities). Such changes need not be independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…Although there are several methodological approaches used in developmental cognitive neuroscience, growth curve models (GCM) represent a powerful analytical framework to model individual differences in cognitive change over time, as well as the variability of patterns of cognitive change between individuals [ 14 ]. In cognitive neuroscience GCMs have been derived using linear mixed effects model (LMEM) or latent curve models (LCM) [ 1 4 , 6 11 , 15 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several methodological approaches used in developmental cognitive neuroscience, growth curve models (GCM) represent a powerful analytical framework to model individual differences in cognitive change over time, as well as the variability of patterns of cognitive change between individuals [ 14 ]. In cognitive neuroscience GCMs have been derived using linear mixed effects model (LMEM) or latent curve models (LCM) [ 1 4 , 6 11 , 15 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cognitive neuroscience GCMs have been derived using linear mixed effects model (LMEM) or latent curve models (LCM) [ 1 4 , 6 11 , 15 23 ]. LCM uses factor analysis and structural equation models for unobserved outcomes [ 14 , 24 ] and are best suited for complex models with straightforward large data structures [ 25 ]. The flexibility of the LCM approach in incorporating variables with high degree of inter-individual variability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Parmi les études examinées dans ce travail, seulement 20% ( La présente étude a établi un état des lieux des trajectoires de déclin fonctionnel de l'autonomie fonctionnelle. Les nombreux défis théoriques et méthodologiques de la recherche sur les parcours de vie exigent des outils statistiques souples (GHISLETTA et al 2015). Ainsi les familles de modèles statistiques pour l'analyse de données longitudinales dont l'analyse de trajectoire de classes latentes, la modélisation linéaire hiérarchique, le modèle de mélange de croissance généralisé à effet aléatoire et beaucoup d'autres méthodes sont des modèles statistiques de changement qui ont imprégné de nombreuses disciplines scientifiques (COLLINS 2006) (DUNCAN et al 2013.…”
Section: Discussionunclassified
“…However, earlier studies have not found support for an interaction between physical workload and job control [ 39 ]. Multivariate models and more stratified analyses, for example, should be employed to further investigate the relationship between physical working conditions, job control, and health [ 40 ].…”
Section: Discussionmentioning
confidence: 99%